2021
DOI: 10.1177/20587384211054036
|View full text |Cite
|
Sign up to set email alerts
|

Curative role of mesenchymal stromal cells in chronic pancreatitis: Modulation of MAPK and TGF-β1/SMAD factors

Abstract: Background and objective: Living organisms respond to physical, chemical, and biological threats with a potent inflammatory response which alters organ cell signaling and leads to dysfunction. We evaluated the therapeutic effect of bone marrow-based mesenchymal stromal cell (BM-MSC) transplanted in rats to preserve tissue integrity and to restore homeostasis and function in the pancreatitis experimental pattern. Methods: This study involved 40 adult male Wister rats. Repeated L-arginine injections caused chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Studies have shown that a large number of inflammatory factors, such as IL-18, TNF-α, and growth factor TGF-B1 are significantly reduced in animal models of CP treated with MSCs, and tissue immune cell infiltration is alleviated. In vitro experiments also showed that when co-cultured with MSCs, the production of inflammatory factors in acinar cells and PSCs was inhibited and the inflammatory response of macrophages was reduced ( 65 70 ).…”
Section: Research Progress Of Anti-inflammatory and Anti-fibrotic The...mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that a large number of inflammatory factors, such as IL-18, TNF-α, and growth factor TGF-B1 are significantly reduced in animal models of CP treated with MSCs, and tissue immune cell infiltration is alleviated. In vitro experiments also showed that when co-cultured with MSCs, the production of inflammatory factors in acinar cells and PSCs was inhibited and the inflammatory response of macrophages was reduced ( 65 70 ).…”
Section: Research Progress Of Anti-inflammatory and Anti-fibrotic The...mentioning
confidence: 99%
“…Pancreatic histopathology showed that MSC treatment improved collagen deposition, repaired damaged cells and Langerhans giant cells, reduced the expression of α-SMA, and reduced immune cell infiltration. Serum analysis showed that MSCs affected ECM metabolism by decreasing levels of hyaluronic acid and fibronectin ( 69 , 70 ). Activation of PSCs is a key link that leads to pancreatic fibrosis.…”
Section: Research Progress Of Anti-inflammatory and Anti-fibrotic The...mentioning
confidence: 99%
See 2 more Smart Citations
“…Mesenchymal stromal cells (MSCs) have therapeutic potential due to their immunoregulatory and antiin ammatory effects [15][16][17][18]. Overexpressing alpha-1 antitrypsin (AAT) in MSCs shows promise in antiin ammatory properties.…”
Section: Introductionmentioning
confidence: 99%